The Impact Of Market Knowledge On Marketing Performance (A Field Study In Food Industries Companies Operating In Damascus And Its Countryside) - صقور, مجد; الشريف, بتول (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This paper aims to study the effect of market knowledge on marketing performance in food industry companies operating in Damascus and its countryside by studying the relationship between the independent variable, which is market knowledge in its three dimensions (knowledge of customers, knowledge of competitors, market research), and the dependent variable, which is marketing performance. The research adopted quantitative approach and positivism philosophy besides deductive approach as scientific methodology for the research. The research population included employees working in all food industry companies in Damascus and its countryside, (155) questionnaires were distributed, (127) questionnaires were responded, the response rate was (81.9%). The study reached the following results: First, the research found a positive and statistically significant relationship between knowledge of customers and knowledge of competitors on the one hand and marketing performance on the other hand, Second, there is no statistically significant relationship between market research and marketing performance.